2008
DOI: 10.1007/s12038-008-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

Branch-point stoichiometry can generate weak links in metabolism: the case of glycine biosynthesis

Abstract: Although the metabolic network permits conversion between almost any pair of metabolites,this versatility fails at certain sites because of chemical constraints (kinetic,thermodynamic and stoichiometric) that seriously restrict particular conversions. We call these sites weak links in metabolism,as they can interfere harmfully with management of matter and energy if the network as a whole does not include adequate safeguards. A critical weak link is created in glycine biosynthesis by the stoichiometry of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…decrease in the need for the methyl group as a result of lower rate of creatine synthesis (Stead LM et al 2001). As discussed by Melendez-Hevia and colleagues (2008) and by Hofmeyr and Cornish-Bowden (2000), the stoichiometry of glycine biosynthesis from serine via glycine hydroxyl methyl transferase and its disposal via consumption of C1 units transferred via THF, results in unique metabolic constraints so that the rate glycine biosynthesis cannot exceed the flux of consumption of the methyl groups via THF or that they are closely linked. Based upon this analysis, we attribute the lower rate of glycine synthesis following creatine supplement to the decrease in the demand for glycine and for methyl groups for creatine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…decrease in the need for the methyl group as a result of lower rate of creatine synthesis (Stead LM et al 2001). As discussed by Melendez-Hevia and colleagues (2008) and by Hofmeyr and Cornish-Bowden (2000), the stoichiometry of glycine biosynthesis from serine via glycine hydroxyl methyl transferase and its disposal via consumption of C1 units transferred via THF, results in unique metabolic constraints so that the rate glycine biosynthesis cannot exceed the flux of consumption of the methyl groups via THF or that they are closely linked. Based upon this analysis, we attribute the lower rate of glycine synthesis following creatine supplement to the decrease in the demand for glycine and for methyl groups for creatine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Glycine, which is 33% of collagen residues, has been typically classified as a ‘non-essential’ amino acid because human metabolism can synthesize it from serine. However, in previous work (Meléndez-Hevia and de Paz-Lugo 2008 ) we have shown that the glycine synthesis pathway has a strong stoichiometric restriction that limits its production, independently of the capacity and the regulatory mechanisms of the enzymes, as shown in Fig. 1 .…”
Section: Introductionmentioning
confidence: 90%
“…e Set of pathways that use glycine as metabolite for other biosynthesis processes. See Meléndez-Hevia and de Paz-Lugo ( 2008 ) …”
Section: Introductionmentioning
confidence: 99%
“…Glycine is a nonessential proteinogenic AA, primarily utilized in the synthesis of collagen, with limited function in the synthesis of other proteins and metabolic pathways [22]. Previous work by Meléndez-Hevia and de Paz-Lugo [23] suggests that a restriction in the stoichiometry of the glycine synthesis reaction may lead to insufficient glycine production relative to metabolic demand, making glycine an essential or conditionally essential AA. The CLV feeding system produced both ideal whey and acid whey with significantly higher concentrations of cysteine than the TMR system.…”
Section: Total Amino Acid Compositionmentioning
confidence: 99%